Analisis Pengaruh Ekspor, UMP, dan PMA Terhadap PDRB di Provinsi Jawa Timur - Nichauri Elsa Maysari (Jurnal Ilmu Ekonomi, 2022)
This study aims to determine how the influence of Export Value, Provincial Minimum Wage, Foreign Investment on Gross Regional Domestic Product in East Java Province. The analytical tool used is time series data regression with hypothesis testing, namely the F test, T test and the coefficient of determination R2. The results show that the export value has a significant positive effect where the coefficient value is 5.996027 with a probability value of 0.0008, the Provincial Minimum Wage has a significant positive effect where the coefficient value is 0.949262 with a probability value of 0.0000 and Foreign Investment has a positive and insignificant impact. where the coefficient value is 9.624246 with a probability value of 0.4149 to the Gross Regional Domestic Product of East Java.